Psychoeducational Approach of Vygotsky and its Relationship with the Symbolic Interactionism: Application to the Juvenile Criminal Responsibility and Educational Processes - Alberto De Rosa, Pablo (2018)
The psychoeducational intellectual work of Lev Vygotsky (1896-1943) provides a theoretical and sociohistorical meaning that allows you to see from a contextualized perspective the higher forms of self- regulation, conscious control and forms of self-governance. This contribution to the theory of the psychology of education is clearly consistent with the conclusions of the interaction approaches that have been developed by the sociology of the Chicago School (George Mead, 1863-1931), proposing the concept of “Symbolic Interactionism” (Herbert Blumer, 1900-1987), to explain the essentially social nature of the person and his actions, which were consolidated in the field of criminology. From the recognition of the pedagogical-educational purpose that is assigned to the process and juvenile criminal sanction, the present essay aims to use the socio- historical theoretical (Vygotsky) and interactionist (Mead-Blumer) reasoning, to think about the importance and influence they have in the setting of goals of the juvenile criminal system and how the criminal and educational processes have a high impact on the formation of subjectivities. In this way, it will state that the process of educational formation is an essential instrument of socialization and humanization of the subject.